AIP Conference Proceedings 2008
DOI: 10.1063/1.3076825
|View full text |Cite
|
Sign up to set email alerts
|

Gamma rays from star-forming regions

Abstract: Abstract. Star-forming regions have been tentatively associated with gamma-ray sources since the early days of the COS B satellite. After the Compton Gamma-Ray Observatory, the statistical evidence for such an association has became overwhelming. Recent results from Cherenkov telescopes indicate that some high-energy sources are produced in regions of active star formation like Cygnus OB2 and Westerlund 2. In this paper I will briefly review what kind of stellar objects can produce gamma-ray emission in star-f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…For instance, the Herbig-Haro objects HH 219 (Hewitt et al 2012) and HH 80-81 (Yan et al 2022) have been identified as potential GeV sources. Efficient particle acceleration in star-forming regions is also expected to arise from the combined action of several protostars and young stellar clusters (Romero 2008), or by the collective action of the stellar winds of young A195, page 8 of 10 Duvidovich, L., and Petriella, A.: A&A proofs, manuscript no. aa45819-22 massive stars and SNRs within super-bubbles (Aharonian et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Herbig-Haro objects HH 219 (Hewitt et al 2012) and HH 80-81 (Yan et al 2022) have been identified as potential GeV sources. Efficient particle acceleration in star-forming regions is also expected to arise from the combined action of several protostars and young stellar clusters (Romero 2008), or by the collective action of the stellar winds of young A195, page 8 of 10 Duvidovich, L., and Petriella, A.: A&A proofs, manuscript no. aa45819-22 massive stars and SNRs within super-bubbles (Aharonian et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A signature of high-energy emission is nonthermal radio emission because particles from the same population are likely to be involved in processes at both energy ranges, at the radio through synchrotron process, and at VHE emission through inverse-Compton scattering. Moreover, the determination of counterparts of gamma-ray sources through radio observations in star-forming regions will help to clarify the role of young stars and collective wind effects in the acceleration of galactic cosmic rays (e.g., Romero et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Radio observations of protostars reveal thermal elongated jets. Strong shock waves created at end of the jets can accelerate charged particles [27]. The maximum energy to which particles are accelerated by these shock waves at the terminal ends is 3 TeV for the electrons and 60 TeV for the protons [27].…”
Section: Star Forming Regionsmentioning
confidence: 99%
“…Strong shock waves created at end of the jets can accelerate charged particles [27]. The maximum energy to which particles are accelerated by these shock waves at the terminal ends is 3 TeV for the electrons and 60 TeV for the protons [27]. Another process for particle acceleration could be due to colliding wind binaries after early massive stars are formed.…”
Section: Star Forming Regionsmentioning
confidence: 99%
See 1 more Smart Citation